Comparison Of Efficacy In Performing Epley’s Maneuver Alone Versus Betahistine Along With Epley’s In Diagnosed Patients Of Benign Paroxysmal Positional Vertigo - Javaid, Amna; Chaudhry, Sadia; Alamgir, Ashar; Imtiaz, Nimra; Haroon, Maliha; Kouser, Amna (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the effectiveness of Epley’s manoeuvre alone and Betahistine with Epley’s in patients with Benign paroxysmal positional vertigo. Methods: After the ethical approval from the institutional review board, this comparative study was conducted at the Department of Otorhinolaryngology Head and Neck Surgery, District Headquarters Hospital, Rawalpindi, Rawalpindi Medical University, Rawalpindi, from February 2024 to August 2024. Through the non-probability consecutive sampling, 60 patients aged between 18-65 years, of either gender, with Vertigo who got a positive Dix-Hallpike test were included in the present study. After the informed consent form, patients were randomly divided into two study groups: Group A-Betahistine + Epley’s (n=30) and Group B- Epley’s (n=30). Results: After 10 days of follow-up, only one patient in Group A remained positive for the Dix-Hallpike test, in contrast to 11 patients in Group B, demonstrating a statistically significant improvement in Group A (P<0.0001). On the first day, the mean Vertigo Symptom Scale (VSS) score was 12.6±3.6 in Group A and 14.6±3.03 in Group B, with Group A exhibiting significantly lower symptom severity (P<0.0001). Furthermore, the mean reduction in VSS score was greater in Group A (8.2±3.3) compared to Group B (7.3±2.6), also showing a statistically significant difference (P=0.042). Conclusion: The use of Betahistine in conjunction with Epley’s maneuver outperforms the application of Epley’s maneuver alone in the treatment of BPPV Keywords: Vertigo, Epley’s, Dix Hall Pike, VSS, betahistine